2015
DOI: 10.1007/s00268-015-3242-y
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Scan and Functional Adrenal Tumors: A Pilot Study for Lateralization

Abstract: Differential 18F-FDG PET/CT uptake was observed in patients with nonfunctioning, aldosterone-hypersecreting, and cortisol-secreting masses. GLUT3 overexpression in cortisol-secreting tumor likely accounts for the differential uptake. Future larger cohort studies will need to be conducted to determine if 18F-FDG PET/CT uptake can lateralize cortisol-secreting adrenal masses in patients with bilateral adrenal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
13
2
1
Order By: Relevance
“…In contrast with Pattel et al [17] no correlation was found between Tmx or Tmx:Lmx and hormonal status. This result could be explained by the differences in the study population.…”
Section: Accepted Manuscriptcontrasting
confidence: 77%
See 3 more Smart Citations
“…In contrast with Pattel et al [17] no correlation was found between Tmx or Tmx:Lmx and hormonal status. This result could be explained by the differences in the study population.…”
Section: Accepted Manuscriptcontrasting
confidence: 77%
“…secreting adrenocortical masses and 12 mm in Conn adenomas). They identified 16 cortisol-secreting masses with a higher average SUVmax (5.9) than 11 nonfunctioning adrenocortical masses (4.2) or than 5 Conn adenomas (3.2); no correlation between tumor size and Tmx was observed [17] as in our study. The authors demonstrated that the 18 F-FDG uptake in cortisol-secreting tumors is higher than in nonfunctioning adrenal masses, in contrast with our experience.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Adrenal adenomas typically do not show increased 18 F-FDG activity, although lipid-poor and functioning adenomas have been reported to show mild 18 F-FDG avidity [1, 2]. Setting a specific SUV threshold in order to differentiate adenomas from malignant adrenal tumors can be misleading.…”
mentioning
confidence: 99%